(untitled) (Sustainability in Debate, 2016)
We discuss the use of knowledge in sustainable economic development. The survey was drawn from the mapping of five companies that work with information technologies. The goal was to analyze qualitatively the relevance of these enterprises in the economic scenario of each country of origin and the way they deal with "knowledge" as a product. Results showed that all companies studied made investments in the qualification of their work teams and in the management of the quality of products and services. We conclude that there is still much room for the growth of information technology in Brazil, mainly through investments in innovation strategies.